Kehadiran Kyai Independen dalam Dinamika Sosial-Politik: Telaah Peran Kyai dalam Merespon Perpolitikan Era Reformasi - Sahlan, Asmaun (el Harakah: Jurnal Budaya Islam, 2004)
Actually there are some people expect the position and role of independent standing kyai do not participate in practical political activities, not contaminated by frenzied and hot politics. The presence of kyai is expected to provide coolness and peace and cool the heat of political flow. Besides, it is also a force of politics and government life in Indonesia. This paper describes the variations and typology of kyai, and the relationship between religion and politics. Kyai that join the flow of politics is always suspected by groups that are not in line with it. The independent kyai that is not contaminated by politics is always waiting for the community. The kyai's decision to engage in politics or not is basically meant to build a just and prosperous community. Sebenarnya ada sebagian masyarakat mengharapkan posisi dan peran kyai berdiri independen tidak ikut dalam kegiatan politik praktis, tidak terkontaminasi oleh hingar-bingar dan panasnya perpolitikan. Kehadiran kyai ini diharapkan dapat memberikan kesejukan dan kedamaian serta mendinginkan panasnya arus politik. Selain itu juga menjadi force kehidupan perpolitikan dan pemerintahan di Indonesia. Tulisan ini menjabarkan mengenai variasi dan tipologi kyai, serta hubungan antara agama dan politik. Kyai yang ikut arus politik selalu dicurigai oleh kelompok yang tidak sejalan dengannya. Adapun kyai independen yang tidak terkontaminasi politik selalu dinantikan masyarakat. Keputusan kyai untuk terlibat politik atau tidak pada dasarnya dimaksudkan untuk membangun umat yang adil dan makmur.